Ascorbic acid, sucrose and olive oil lipids mitigate the inhibitory effects of pectin on the bioaccessibility and Caco-2 cellular uptake of ferulic acid and naringenin. Issue 5 (29th April 2020) - Kruger, Johanita; Sus, Nadine; Frank, Jan
Abstract : Sucrose and olive oil successfully negate the inhibitory effect of pectin on the overall in vitro availability of ferulic acid and naringenin by substantially increasing the bioaccessibility and not cellular uptake of the phenolics. Abstract : Whole fruit and vegetable consumption is universally promoted as healthy, to a large extent due to their high contents of phytochemicals, including phenolics and dietary fibre. The major fibre in fruits and vegetables, pectin, however also decreases the bioavailability of phenolics and carotenoids. While ascorbic acid, sucrose and olive oil lipids may increase the bioavailability of various phenolics, their effects in the presence of pectin have not been investigated. This study aimed to evaluate the modulating effects of sucrose (5.0%), ascorbic acid (0.1%) and olive oil (2.5%) on the inhibition by pectin (2.0%) of ferulic acid and naringenin bioaccessibility and Caco-2 cellular uptake. Pectin reduced the bioaccessbility of ferulic acid and naringenin, by 45 and 65%, respectively. Sucrose mitigated the inhibitory effect of pectin and increased naringenin bioaccessbility from 7.9 to 15.0%. When added to digestions with ferulic acid and pectin, sucrose and olive oil totally negated pectin's bioaccessibility inhibition. The Caco-2 cellular uptake of bioaccessible ferulic acid was high (58.3%) and pectin and ascorbic acid together increased it to 85.6%. The Caco-2 cellular uptake of bioaccessible naringenin was also high (47.0%) and pectin increased it to 95.0%. Sucrose and olive oil for ferulic acid and only sucrose for naringenin totally negated the inhibitory effect of pectin on the overall in vitro availability (cellular uptake as percentage of amount of phenolic initially digested). The ameliorating effects of sucrose and olive oil are due to substantially increased bioaccessibility of the phenolics, probably due reduced encapsulation of the phenolics in pectin.